Histoplasmosis: diagnostic challenges - María Guadalupe Frías-De León (Case Reports)
Histoplasmosis is an infection usually caused by a fungal pathogen that, in most cases, occurs in the respiratory tract, which explains the high frequency of clinical manifestations in the lungs. (1) This mycosis is endemic in the Americas (Mississippi and Ohio River Valley, USA; Central and South America; and the West Indies), while reports in areas of Asia, Africa, Australia, and Oceania are mainly associated with the pandemic of acquired immune deficiency syndrome (AIDS). In Europe, cases are on the rise because of the speculation of a global distribution of histoplasmosis, and emphasis has been on improving methods for its diagnosis. (2,3)